Stylistic Analysis of Maya Angelou’s Equality - arina isti'anah (Bina Nusantara University, 2017)
This research presented the stylistic analysis of a poem by Maya Angelou, Equality. The poem was chosen as it became Angelou’s one of well-known poems. The Stylistic analysis aimed at comprehending the meanings of either literary or non-literary text by means of observing the language device used in the texts. In this article, the stylistic analysis was conducted to analyze Maya Angelou’s Equality. To achieve the goal of stylistic analysis, there were some language levels to observe; they were phonological, graphological, grammatical, and semantic levels. In the phonological level, the repetition of rhyme in some stanzas, assonance, consonance, and alliteration were used to voice Angelou’s dream about freedom for black people. In the graphological level, the use of prominent punctuation in stanzas 3, 6, and 9 stressed equality as the requirement for the freedom she expected. In the grammatical level, Angelou used pronoun I and you as the dominant words in the poem, revealed different class the poet experienced in the country. The use of metaphors in the poem brought the same meaning as freedom, voice, effort, and racism that black people experienced in America. This research concludes that stylistics applies to analyze literary work so that thorough appreciation to it can be achieved.